2011
DOI: 10.1016/j.jacc.2011.10.851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Coronary Artery Disease and Adverse Events Among Symptomatic Patients With Coronary Artery Calcification Scores of Zero Undergoing Coronary Computed Tomography Angiography

Abstract: In symptomatic patients with a CAC score of 0, obstructive CAD is possible and is associated with increased cardiovascular events. CAC scoring did not add incremental prognostic information to CCTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
153
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 338 publications
(192 citation statements)
references
References 21 publications
13
153
3
3
Order By: Relevance
“…That almost half our cohort demonstrated noncalcified plaques highlights an important advantage of coronary CTA over calcium scoring alone, suggesting that asymptomatic OSA patients undergoing cardiovascular evaluation should have coronary CTA rather than calcium scoring if true plaque burden is to be assessed. Other studies have also found substantial plaque burden and a negative coronary calcium score in at-risk groups [33]. Although conjectural, our finding of a substantially higher prevalence of plaques in proximal coronary segments in high-AHI patients may have outcome implications, such proximal plaques are strongly associated in other high-risk groups with subsequent adverse cardiac events [34].…”
Section: Discussionsupporting
confidence: 44%
“…That almost half our cohort demonstrated noncalcified plaques highlights an important advantage of coronary CTA over calcium scoring alone, suggesting that asymptomatic OSA patients undergoing cardiovascular evaluation should have coronary CTA rather than calcium scoring if true plaque burden is to be assessed. Other studies have also found substantial plaque burden and a negative coronary calcium score in at-risk groups [33]. Although conjectural, our finding of a substantially higher prevalence of plaques in proximal coronary segments in high-AHI patients may have outcome implications, such proximal plaques are strongly associated in other high-risk groups with subsequent adverse cardiac events [34].…”
Section: Discussionsupporting
confidence: 44%
“…This is in contrast to the results of the Coronary CT Angiography Evaluation for Clinical Outcomes (CONFIRM) registry, 7 in which symptomatic patients with a CACS of 0 AU had the same MACE rate as those with positive CACS values. It has to be noted, however, that the CONFIRM findings concerned only a small group of patients (1.8%) in whom obstructive coronary lesions were present.…”
contrasting
confidence: 95%
“…Finally, although rare, significant coronary stenosis may be caused by noncalcified plaque in patients with CAC scores of 0. 20 As the correlation between CAC score and Adjusted for the effects of age, sex, body mass index, and traditional risk factors, which were significant in univariate analysis (diabetes mellitus and hypertension). CAC indicates coronary artery calcium (reference, CAC 0); CI, confidence interval; and OR, odds ratio.…”
Section: Discussionmentioning
confidence: 99%